A Modified Free-Will Defense: A Structural and Theistic Free-Will Defense as a Response to James Sterba - Balci, Elif Nur (Religions, 2022)
In his book Is a Good God Logically Possible?, James Sterba argues that the Plantingian free-will defense, which reconciles the existence of a good and omnipotent God with the existence of evil, is a failed argument when it comes to the terrible evils in the world. This study discusses that Sterba’s claim is invalid when Plantinga’s free-will defense is modified with a structural perspective. In order to reconcile the structural and inevitable possibility of evil with God’s moral imperatives, a structural free-will defense was complemented by an Islamic moral theology that Mu’tazila and its great scholar Qādi Abd al-Jabbar advanced. Such a modified free-will defense can show that the existence of all evil, including terrible ones, is still compatible with a good and omnipotent God.